Galectin-3- Mediated Transdifferentiation of Pulmonary Artery Endothelial Cells Contributes to Hypoxic Pulmonary Vascular Remodeling - Li Zhang; Yu-mei Li; Xi-xi Zeng; Xiao-yan Wang; Shao-kun Chen; Long-xin Gui; Mo-Jun Lin (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Vascular muscularity is a key event in vessel remodeling during pulmonary artery hypertension (PAH). Endothelial-mesenchymal transdifferentiation (EndMT) has been increasingly reported to play a role in disease occurrence. Galectin-3, a carbohydrate-binding protein regulates cell proliferation, differentiation, migration and neovascularization. However, whether galectin-3 controls endothelial cell transdifferentiation during the development of PAH is unknown. Methods: Rats were exposed to normoxic or hypoxic conditions (fraction of inspired O2 0.10) for 21 d to establish PAH models. Hemodynamic changes were evaluated through surgery of the right jugular vein and ultrasound biomicroscopy inviVue. And vessel pathological alterations were detected by H&E staining. Galectin-3 (Gal-3)-induced pulmonary artery endothelium cell (PAEC) dynamic alterations were measured by MTT assays, Cell immunofluorescence, Flow cytometry, Real-time PCR and Western blot. Results: Our study demonstrated that Gal-3 was expressed in hypoxic pulmonary vascular adventitia and intima. The increased Gal-3 expression was responsible for hypoxic vessel remodeling and PAH development in vivo. Gal-3 was found to inhibit cell proliferation and apoptosis in cultured endothelial cells. Meanwhile endothelial cell morphology was altered and exhibited smooth muscle-like cell features as demonstrated by the expression of α-SMA after Gal-3 treatment. Gal-3 activated Jagged1/Notch1 pathways and induced MyoD and SRF. When MyoD or SRF were silenced with siRNAs, Gal-3-initiated transdifferentiation in endothelial cells was blocked as indicated by a lack of α-SMA. Conclusion: These results suggest that Gal-3 induces PAECs to acquire an α-SMA phenotype via a transdifferentiation process which depends on the activation of Jagged1/Notch1 pathways that mediate MyoD and SRF expression.